2018
DOI: 10.1038/s41598-018-20824-0
|View full text |Cite
|
Sign up to set email alerts
|

Evoked and oscillatory EEG activity differentiates language discrimination in young monolingual and bilingual infants

Abstract: Language discrimination is one of the core differences between bilingual and monolingual language acquisition. Here, we investigate the earliest brain specialization induced by it. Following previous research, we hypothesize that bilingual native language discrimination is a complex process involving specific processing of the prosodic properties of the speech signal. We recorded the brain activity of monolingual and bilingual 4.5-month-old infants using EEG, while listening to their native/dominant language a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 45 publications
(88 reference statements)
2
30
0
Order By: Relevance
“…When appropriate analyses techniques are applied for group-level statistical comparison, no differences emerged between our monolingual and bilingual infants’ RSFC at 4 months of age. In light of previous research that demonstrated neural adaptation in bilingual infants in linguistic tasks at this age (e.g., Nacar-Garcia et al, 2018), our results suggest that intrinsic functional networks of the brain are not affected by bilingual experience during the earliest stages of life. Further, considering previously reported differences in adult monolingual vs. bilingual RSFC patterns (e.g., Luk et al, 2011; Grady et al, 2015; Berken et al, 2016), at what stage of development RSFC begin to show changes depending on language environment is open for future research.…”
Section: Discussionsupporting
confidence: 74%
“…When appropriate analyses techniques are applied for group-level statistical comparison, no differences emerged between our monolingual and bilingual infants’ RSFC at 4 months of age. In light of previous research that demonstrated neural adaptation in bilingual infants in linguistic tasks at this age (e.g., Nacar-Garcia et al, 2018), our results suggest that intrinsic functional networks of the brain are not affected by bilingual experience during the earliest stages of life. Further, considering previously reported differences in adult monolingual vs. bilingual RSFC patterns (e.g., Luk et al, 2011; Grady et al, 2015; Berken et al, 2016), at what stage of development RSFC begin to show changes depending on language environment is open for future research.…”
Section: Discussionsupporting
confidence: 74%
“…We suggest that as a consequence of this, amplitude tracking subsides in the native language, as infants shift their focus from larger units (syllables) to smaller units (phonemes) in order to attune to the sound patterns of their native language. A prediction of this claim is that gamma oscillations, believed to be responsible for (sub)phonemic processing, are enhanced between birth and 6 months, especially for the native language – a prediction that is currently being investigated in our laboratory following upon existing work on this question ( Peña et al, 2010 ; Ortiz-Mantilla et al, 2013 ; Nacar Garcia et al, 2018 ). Subsequently, amplitude tracking in the native language reappears, possibly once word and grammar learning are well underway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the fact that this source of information can only be a rough approximation of infants' exposure to the languages, there is some disagreement across different researchers where the boundary between mono- and bilingual development should be set. In some studies, 20% of exposure to another language is considered as the upper limit for being treated as a monolingual infant (Garcia et al, 2018), other studies take 20% exposure to another language as the lower limit of being considered a bilingual infant (Liu & Kager, 2017). Future research in infant bilingualism should use a common criterion and more comparable assessments of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Bilingual infants' discrimination between their native languages and two other non-native languages was also investigated using EEG (Narca Garcia, Guerrero-Mosquera, Colomer & Sebastián-Gallés, 2018). Four-month-old monolingual Spanish or Catalan and bilingual Catalan–Spanish infants were presented with Catalan, Spanish, Italian and German sentences.…”
Section: Initial Speech Perception Abilitiesmentioning
confidence: 99%